2005
DOI: 10.1071/ar04143
|View full text |Cite
|
Sign up to set email alerts
|

Ascochyta blight of chickpea (Cicer arietinum L.): a review of biology, pathogenicity, and disease management

Abstract: Ascochyta blight (AB), caused by Ascochyta rabiei is a major disease of chickpea (Cicer arietinum L.), especially in areas where cool, cloudy, and humid weather persists during the crop season. Several epidemics of AB causing complete yield loss have been reported. The fungus mainly survives between seasons through infected seed and in infected crop debris. Despite extensive pathological and molecular studies, the nature and extent of pathogenic variability in A. rabiei have not been clearly established. Accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
199
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(211 citation statements)
references
References 66 publications
3
199
1
Order By: Relevance
“…Breeding of chickpea for resistance to AB is an important goal worldwide but is often limited due to the absence of high levels of resistance in chickpea germplasm which along with the highly variable pathogen, has precluded the development of varieties with both high and durable resistance (Knights and Siddique 2002;Pande et al 2005;Chen et al 2004, Tivoli et al 2006. The ICARDA scientists have developed more than 3000 lines with moderate resistance to AB (Malhotra et al 2003), but the frequency of highly resistant lines to AB is generally low (Iqbal et al 2002;Atanasova and Mihov 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Breeding of chickpea for resistance to AB is an important goal worldwide but is often limited due to the absence of high levels of resistance in chickpea germplasm which along with the highly variable pathogen, has precluded the development of varieties with both high and durable resistance (Knights and Siddique 2002;Pande et al 2005;Chen et al 2004, Tivoli et al 2006. The ICARDA scientists have developed more than 3000 lines with moderate resistance to AB (Malhotra et al 2003), but the frequency of highly resistant lines to AB is generally low (Iqbal et al 2002;Atanasova and Mihov 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Using this growth room facility, components of controlled environment screening techniques (seedling screening technique and cut-twig screening technique) for AB evaluation were optimized. Large number of chickpea genotypes have been screened using this seedling screening technique at ICRISAT and currently the technique is being extensively used for AB resistance evaluation (Pande et al 2005;.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenic fungus Ascochyta rabiei is responsible for chickpea blight. This fungus attacks the crop in areas where humid and cool weather persists, and causes great yield loss (Pande et al, 2005). The most common and effective method for the control of chickpea blight is the application of fungicides, such as mancozeb, chlorothalonil, and triphenyltin hydroxid.…”
Section: Introductionmentioning
confidence: 99%
“…All aerial parts of the host are affected (Nene & Reddy, 1987;Pande et al, 2005) as are both yield and seed quality, and complete yield losses have been reported (Kaiser & Muehlbaur, 1988;Navas-Cortes et al, 1998). The inoculum originates from infected seed and previous season stubble, and secondary infections are spread throughout the crop by rain splash (Pande et al, 2005). Therefore, plants may become infected at a number of stages in their life cycle, dependent on inoculum level and epidemiological conditions.…”
Section: Introductionmentioning
confidence: 99%